The muscle nutritional components analysis of golden pompano (Trachinotus blochii) in different mariculture area, growth stages, and genders - Shi, Liping; Song, Feibiao; Xing, Shuiyao; Zhang, Weiwei; Liang, Yesong; Zhang, Kaixi; Sun, Junlong; Luo, Jian (Frontiers in Nutrition, 2023)
Golden pompano (Trachinotus blochii) is an economically important fish which exhibits sexual size dimorphism and is widely cultivated in the southern seas of China. To evaluate the nutritional composition of T. blochii of different mariculture areas, growth stages, and genders, the moisture, ash, amino acids, and fatty acids in the muscle were measured using national standard biochemical assay.The analysis found 16 kinds of amino acids in the muscle of T. blochii. The EAA contents of fish from Guangdong (GD) and Guangxi (GX) were significantly lower than those of Hainan (HN) and Fujian (FJ) (P < 0.05). The unsaturated fatty acids were higher in T. blochii cultured in HN and FJ (P < 0.05). Within the same sea area, the contents of TAA, EAA, DAA and PUFA increased with growth in T. blochii, but the differences were not significant (P > 0.05). EAA/TAA and EAA/NEAA conformed to the ideal FAO/WHO model. The AAS, CS, and EAAI scores of amino acids within groups gradually increased with growth. The TAA, EAA and PUFA contents in females were higher than in males (P > 0.05). The slightly higher amounts of amino acids and fatty acids in female T. blochii indicated females had higher nutritional value. In conclusion, the HN and FJ groups, the later growth stages, and the female T. blochii had generally higher nutritional values than their respective 2 This is a provisional file, not the final typeset article counterparts. These results provide fundamental data supporting all-female T. blochii breeding and culture, and optimized marketing body size.